Respon Pertumbuhan dan Produksi Tanaman Selada (Lactuca sativa L.) terhadap Pemberian Pupuk Kandang dan Mikroorganisme Lokal (MOL) - Panjaitan, Ernitha; Silaen, Sihar; Damanik, Rio D; Damanik, Rio D. (Universitas Medan Area, 2019)
Organic matter contained in manure fertilizer function to improve soil physical properties, soil chemistry, and soil biology. Local microorganisms from banana weevils contained macro, micro nutrients and contained bacteria which will act as decomposers of organic matter.This research aimed to determine the effect of the combination of manure fertilizer and local microorganisms on the growth and yield of lettuce. The research was conducted on the land of the Faculty of Agriculture, Methodist University, Medan, in March - April 2016, using split plot design, with three replications, 9 combinations to obtain 27 plant plots of all combinations and replications was used in this study. The first factor tested was manure fertilization ie R1= given chicken manure 45 g plant-1, R2 = given cow manure 45 g plant-1 and R3= given goat manure 45 g plant-1. The second factor tested was local microorganisms that was D1 = 30 cc l-1 water), D2 = 40 cc l-1 water and D3= 50 cc l-1 water. The results showed that the treatment of types of manure and local microorganisms in general had a significant effect on the growth and production of lettuce plants. The provision of chicken manure as much as 45g plant-1 (R1) and local microorganisms 50 cc l-1 water (D3) gave a better response to the growth of plant height, number of leaves, amount of chlorophyll and wet lettuce better than other treatments.